SAFETY OF LIGASURE IN THYROIDECTOMY IN COMPARISON WITH CONVENTIONAL SUTURE TIE TECHNIQUE (The Research of Medical Science Review, 2025)
Objectives: To compare the outcomes of LigaSure versus suture tying in patients undergoing total thyroidectomy. Study Design: Comparative observational study. Place and Duration of Study: “Combined Military Hospital, Lahore from January to July 2024”. Methodology: Ninety six patients who underwent total thyroidectomy were divided into LigaSure group and Suture tie group. Outcomes were assessed and compared between groups. SPSS version 20 was used for statistical analysis. Results: Mean age of the patients was 31.72 ± 11.11 years. There were 26 (27.08%) male and 70 (72.92%) female patients. Mean operation time, blood loss during surgery, drain output, drain duration and hospitalization length were significantly shorter in LigaSure group (p < 0.001). There was no statistically significant difference between LigaSure and Suture tie group in terms of frequency of complications (p > 0.05). Conclusion: Better outcomes are achieved after thyroidectomy with use of LigaSure as compared to traditionally used suture tying technique.